2012
DOI: 10.1002/ijc.27781
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen‐activated protein kinase (MEK/ERK) inhibition sensitizes cancer cells to centromere‐associated protein E inhibition

Abstract: Inhibition of centromere-associated protein-E (CENP-E) has demonstrated preclinical anti-tumor activity in a number of tumor types including neuroblastoma. A potent small molecule inhibitor of the kinesin motor activity of CENP-E has recently been developed (GSK923295). To identify an effective drug combination strategy for GSK923295 in neuroblastoma, we performed a screen of siRNAs targeting a prioritized set of genes that function in therapeutically tractable signaling pathways. We found that siRNAs targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…The increased cell death by MEK/paclitaxel combination is associated with the cooperative up-regulation of the pro-apoptotic protein Bim and down-regulation of the anti-apoptotic protein Mcl-1 43 . MEK/ERK inhibition could also sensitize neuroblastoma cells to the inhibitors of centromere-associated protein E (CENP E), a kinesin motor protein that is critical for chromosome attachment to mitotic spindles 44 . Moreover, combined inhibition of MEK and Plk1 elicits synergistic antitumor activity specifically in NRAS mutant melanoma 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The increased cell death by MEK/paclitaxel combination is associated with the cooperative up-regulation of the pro-apoptotic protein Bim and down-regulation of the anti-apoptotic protein Mcl-1 43 . MEK/ERK inhibition could also sensitize neuroblastoma cells to the inhibitors of centromere-associated protein E (CENP E), a kinesin motor protein that is critical for chromosome attachment to mitotic spindles 44 . Moreover, combined inhibition of MEK and Plk1 elicits synergistic antitumor activity specifically in NRAS mutant melanoma 24 .…”
Section: Discussionmentioning
confidence: 99%
“…GSK923295 is an allosteric inhibitor of CENP-E that blocks its microtubule stimulated ATPase activity and stabilizes the interaction between the motor domain and microtubules [449,450]. GSK923295 has demonstrated both in vitro and in vivo antitumor activity against various malignancies [449,451,452,453,454,455]. Cells treated with GSK923925 assemble bipolar spindles and the majority of chromosomes align at the spindle equator.…”
Section: Targeting Chromosome Congression For Cancer Therapymentioning
confidence: 99%
“…However, some chromosomes remain clustered near the spindle poles, leading to mitotic arrest and apoptosis [449,456]. The antitumor activity of GSK923925 has been evaluated in combination with standard chemotherapies, as well as with other emerging targeted drugs [454]. Inhibition of ERK1 revealed a significant synergistic proliferation inhibition activity when combined with GSK923225 in neuroblastoma, lung, pancreatic and colon carcinoma cell lines [454].…”
Section: Targeting Chromosome Congression For Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the ERK signaling pathway which universally governs proliferation, differentiation and cell survival, is associated with resistance to apoptosis in malignant tumors. Many studies showed that inactivation of this pathway sensitizes cancer cells to anti-cancer drugs induced apoptosis, 26,27 and the subject of intense research scrutiny leading to the development of pharmacologic inhibitors for the treatment of cancer. Yao et al 28 demonstrated that Trop-2 has the ability to activate ERK using gene-reporter assays, and Trop-2 expression contributes to tumor by activating the ERK/MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%